Research of the Two-stage Planetary Level Parallel Axis Structure of Wind Power Gearbox Assembly Technology - Zou Junwei; Huang Junqiong; You Jing (Jixie chuandong)
Wind power gearbox assembly process quality has a decisive influence on the wind power gearbox assembly quality,it has important significance for improving the reliability of wind power gearbox.Aiming at the three assembly process difficulties problems of the two-stage planetary level parallel axis structure of wind power gearbox about planetary wheel,planet wheel axial momentum assurance and the measurement,body up and down box after box,surface level degree guarantee.Firstly,the deeply analysis planetary gear assembly parts matching relationship,the principle of bearing axial clearance control,the structure of rear housing,and then,the solution is put forward.Finally,the process scheme is verified.